Seasonal change in growth rate, carrageenan yield and quality from the red alga (Kappaphycus striatus) cultivated in Cam Ranh bay - Hung, Le Dinh; Thi Hoa, Le (Vietnam Journal of Biotechnology, 2021)
The red alga Kappaphycus striatus was cultivated at Camranh Bay, KhanhHoa, Vietnam. For a 30 day cultivation period, the alga showed the higher growth rate (4.1 - 5.8 % day-1) from October 2014 to April 2015 and in September 2015, while the lower growth rate (2.5 - 3.1 % day-1) was found from May to August 2015. The carrageenan quality was done for a 60-day cultivation period, the carrageenan yield and gel strength showed little variation with the higher values (28.1 - 28.7 % and 855 - 935 g cm-2, respectively) obtained from November 2014 to March 2015 and lower ones (25.1 - 26.7 % and 555 - 758 g cm-2, respectively) from April to September 2015. The data on moisture content of alga (33.5 - 36.8 %), clean anhydrous algal/salt ratio (0.92 - 1.07), and carrageenan yield obtained in this study fulfilled those of standards for carrageenophytes. This study shows that the red alga K. striatus can be grown in the tropical waters of the Camranh Bay during the northeast monsoon and a part of the southwest monsoon as a source of materials for carrageenan production.